How Do Patients Define Satisfaction? The Role of Patient Perceptions of Their Participation and Health Provider Emotional Expression. Issue 14 (6th December 2021) - Baker, Susan C.; Watson, Bernadette M.; Jamieson, Barbara; Jamieson, Raymond
ABSTRACT: Patient satisfaction is important to patient outcomes. Previous attempts to conceptualize satisfaction have often taken an atheoretical approach and focused on doctors' communication skills. Patients are becoming more active health consumers involved in their health care and current definitions of patient satisfaction may not accurately reflect patient expectations about their health consultations. Earlier research found that meeting patients' emotional needs – through empathy and patient-centered communication – is important to patient satisfaction. New research is needed to explore how those needs can be met given the changing trend in patient behaviors and the focus on patient-centredness. This study employed two communication theories – the Willingness to Communicate Model and Communication Accommodation Theory – to consider both patients' communicative decisions, and the intergroup features of the health context that can influence communicative behaviors. Two hundred and fifty-three patients from health clinics in Canada and Australia described what satisfaction meant to them, and identified what aspects of their health consultation were satisfying (or not), and we investigated their perceptions of doctor's emotional expression. Results suggest that patient perceptions of their participation in the consultation predicts their perceptions of doctor emotional expression, and their satisfaction with the consultation. Patients want both emotional and medical needs met in an environment that balances interpersonal and intergroup communication. Our findings suggest the need to expand current definitions of patient satisfaction, patient-centredness and emotional expression. We discuss the implications of these findings for health practitioners and consider future research that addresses the need for more individualized health care.